Rangatahi Maori climate action: A dialogue with nature-based solutions - Annie Te One; Diane Menzies; Brittany Pooley; India Logan-Riley (Nature-Based Solutions)
This article explores the broad area of rangatahi Māori climate activism. As a research team made up of academics, rangatahi and rangatahi Māori activists, this perspective piece discusses the importance of whakapapa, belonging and connections to the environment as a foreground to climate activism. While we highlight the lack of academic research focussed on rangatahi Māori climate activism, we show that there is a plethora of activity happening through digital and social media which provides a rich space for sharing innovative ideas for a just future in which nature is centered. We suggest that there are many commonalities between the current articulations of Nature-Based Solutions and rangatahi Māori activism and that greater dialogue between these spaces is vital for any solutions being offered for an environmentally just future for Aotearoa.